Inside Front Cover: Cover Image, Volume 21, Issue 5. Issue 5 (29th August 2018) - Foti, Francesca; Menghini, Deny; Alfieri, Paolo; Costanzo, Floriana; Mandolesi, Laura; Petrosini, Laura; Vicari, Stefano
Abstract : The cover image, by Francesca Foti et al., is based on the Paper Learning by observation and learning by doing in Down and Williams syndromes, DOI: 10.1111/desc.12642 . Funding Credit: The Fondation Jérôme Lejeune to LM (2016B n.1567)